Pendampingan Pembelajaran Matematika Berbantuan GeoGebra pada Materi Geometri tingkat SMA di Pesisir Selatan - Meria Gusteti; Khairul Azmi; Suci Wulandari; Widya Rahmalina; Asrina Mulyati; Ria Finolia; Fitri Miftahurrizky; Haura Qhonitah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
This community service program aimed to implement GeoGebra as a systemic innovation in geometry learning at MAN 2 Pesisir Selatan. The program was designed to address students' visual abstraction barriers and strengthen teachers' pedagogical capacity through interactive mentoring and the utilization of open-source technology. Evaluation was conducted comprehensively using a 10-item student response questionnaire. Descriptive analysis results showed an overall mean score of 3.32, categorized as "Very Good". Findings revealed a Standard Deviation (SD) of 0.063 and a Variance of 0.004, indicating highly homogeneous student responses with no polarization. Pedagogically, GeoGebra proved effective as a cognitive bridge supporting dynamic visualization, strengthening conceptual understanding, and enhancing student learning motivation. This program is recommended to be integrated sustainably into the curriculum for the development of a technological society in the future.